Feasibility and outcomes of the removable prosthesis in medically compromised patients - Al-Hussain, Abdullah F.; Aljabri, Yahya S.; Sindi, Khalid A.; Thobab, Abdulaziz Y.; Khormi, Abdullah A.; Daghreeri, Faisal A.; Bediwi, Raghad M.; Alolaywi, Fawaz S.; Habbal, Nadia H.; AlQahtani, Shoroq M.; Alkhamis, Sana F. (International Journal Of Community Medicine And Public Health, 2021)
Increasing awareness about providing the necessary care of oral health is essential for patients with a removable prosthesis. The awareness is less interested in dental disorders, being busier with the systemic ones. Planning prosthetic management should only be done after a thorough evaluation of the underlying systemic conditions because the treatment plan might vary accordingly. Previous studies have demonstrated that many systemic diseases are associated with removable prosthesis (RP) procedures. We aim to discuss the feasibility and outcomes of the removable prosthesis for medically compromised patients, including many conditions as diabetes mellitus, cardiovascular, renal, hematological, pulmonary, gastrointestinal disorders and immunocompromised patients. Taking adequate care of oral hygiene practices is recommended for these patients. In addition, it is necessary to have frequent care, but short follow-up visits to make sure that the modalities are still valid for additional use, and to investigate for potential complications and adverse events. Adequate prophylaxis against some diseases might also be the only convenient solution. Therefore, proper management of the medical condition might be associated with the enhanced success of the modality with favorable outcomes and better quality of life. Making unified protocols to deal with these patients is also suggested to enhance the practice among the different clinical settings.